1985
DOI: 10.1159/000180051
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Growth Hormone Release by Thyrotropin-Releasing Hormone in Elderly Subjects

Abstract: The effect of thyrotropin-releasing hormone (TRH) on the release of growth hormone (GH) was investigated in 16 elderly male subjects aged 74-88 years. Intravenous injection of 200 µg TRH induced a clear-cut GH rise ( ≧ 10 ng/ml) in 7 of 16 subjects. TRH administration did not raise plasma GH in 10 adult subjects aged 36-58 years. The results suggest disorders in neurobiochemical mechanisms regulating hypothalamopituitary function in elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This unexpected response to nonspecific stimuli was originally described in acromegalic patients ( Irie & Tsushima, 1972) and interpreted as altered receptor expression directly related to the presence of tumoral tissue ( Le Dafniet et al ., 1985 ). A GH response to TRH has also been described in other non‐neoplastic conditions, such as renal failure ( Gonzales‐Barcena et al ., 1973 ), anorexia nervosa ( Maeda et al ., 1976 ), primary hypothyroidism ( Collu et al ., 1977 ), insulin‐dependent diabetes mellitus ( Dasmahapatra et al ., 1988 ), and ageing ( Barreca et al ., 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…This unexpected response to nonspecific stimuli was originally described in acromegalic patients ( Irie & Tsushima, 1972) and interpreted as altered receptor expression directly related to the presence of tumoral tissue ( Le Dafniet et al ., 1985 ). A GH response to TRH has also been described in other non‐neoplastic conditions, such as renal failure ( Gonzales‐Barcena et al ., 1973 ), anorexia nervosa ( Maeda et al ., 1976 ), primary hypothyroidism ( Collu et al ., 1977 ), insulin‐dependent diabetes mellitus ( Dasmahapatra et al ., 1988 ), and ageing ( Barreca et al ., 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a GH response to TRH has been described in pathological conditions, other than acromegaly, including renal failure (22), de¬ pression (23), anorexia nervosa (24), primary hypothyroidism (25), insulin-dependent diabetes mellitus (26), and schizophrenia (27), as well as in aging (28). Adams et al (10) did not exclude that in vitro normal pituitary tissue can respond to TRH with a GH increase.…”
mentioning
confidence: 99%
“…It is shown that the aging process is associated with a pro gressive alteration in biogenic amine systems in selected regions of the brain [22]. In par ticular, the age-related decrease in GH re lease could be related to a reduction of cen tral dopaminergic tonus, as found in old rats [23], The reduced GH rise after L-dopa ad ministration [16], and also the paradoxical GH increase induced by TRH [24], might be explained by a derangement in central dopa minergic tonus. Our experience seems to confirm that some differences in DA control of GH secretion are present in elderly versus young men.…”
Section: Discussionmentioning
confidence: 99%